An Experimentation on Properties of Geo-polymer Concrete with fibres - Sandeep Sathe, Vedang Patil, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Geo-polymer concrete, deemed by the researchers as the new age concrete is considered as a replacement to its conventional counterpart Portland cement concrete. Already a lot of research work has gone into development and opportunities for Geo-polymer concrete or cement less concrete as they call it. Everyone is now vary of the environmental impact of usage of cement and still it is worldwide the most broadly used constituent for almost all construction purposes. Geo-polymer concrete uses pozzolans and other cementitious materials to replace completely the Portland cement that is used on a large scale for producing concrete. Apart from water it uses solutions known as alkali activators to react with the source materials to form geocement through a process called Geo-polymerization. This Geo-polymer concrete has been studied by researchers in the past years and these studies conclude that Geo-polymer concrete is superior to the cement concrete from the structural and durability consideration. But Geo-polymer concrete suffers from some major drawbacks like being weak in tension just like its conventional counterpart and it needs accelerated curing for gaining its high early strength. In this research, we had understood the result of different fibres on the inherent properties of Geo-polymer concrete.